Estimating the Total Number of Workplace and Public Electric Vehicle Chargers in California. Issue 12 (December 2021) - Xu, Bingzheng; Davis, Adam Wilkinson; Tal, Gil
Allocating charging infrastructure to support the plug-in electric vehicle (PEV) market transition is a major challenge for policy makers and planners seeking to promote PEV adoption. Most electric vehicle charging away from home takes place at or near the workplace, but existing research is focused on public charging. This study developed a method to combine charging location data from a variety of sources including users' self-reports to produce a combined database of workplace and public charging locations. By matching survey responses to charging locations reported in other datasets using spatial clustering methods, we estimated the number of charging locations and chargers in California. This analysis found that charger location datasets from the Alternative Fuels Data Center and Plugshare included many of the same charging locations as each other but missed many chargers that serve commuters; as a result, existing datasets significantly underrepresent the total number of chargers in California. Some 28, 175 Level 2 chargers and 7, 350 direct current fast chargers by were identified by combining charger location data from the Alternative Fuels Data Center and Plugshare and at least 27, 000 additional chargers near commute destinations by adding locations reported in a survey of electric vehicle drivers.